Chitosan functionalisation of gold nanoparticles encourages particle uptake and induces cytotoxicity and pro-inflammatory conditions in phagocytic cells, as well as enhancing particle interactions with serum components. Issue 1 (December 2015) - Boyles, Matthew; Kristl, Theresa; Andosch, Ancuela; Zimmermann, Mirjam; Tran, Ngoc; Casals, Eudald; Himly, Martin; Puntes, Victor; Huber, Christian; Lütz-Meindl, Ursula; Duschl, Albert
Abstract Background Gold nanoparticles (AuNPs) are a popular choice for use in medical and biomedical research applications. With suitable functionalisation AuNPs can be applied in drug delivery systems, or can aid in disease diagnosis. One such functionalisation is with chitosan, which enables efficient interaction and permeation of cellular membranes, providing an effective adjuvant. As both AuNPs and chitosan have been shown to have low toxicity and high biocompatibility their proposed use in nanomedicine, either individually or combined, is expanding. However, further toxicological and immunological assessments of AuNP-chitosan conjugates are still needed. Therefore, we have evaluated how AuNP functionalisation with chitosan can affect uptake, cytotoxicity, and immunological responses within mononuclear cells, and influence the interaction of AuNPs with biomolecules within a complex biofluid. The AuNPs used were negatively charged through citrate-coating, or presented either low or high positive charge through chitosan-functionalisation. Uptake by THP-1 cells was assessed via transmission electron microscopy and electron energy loss spectroscopy, pro-inflammatory responses by ELISA and qRT-PCR, and cell death and viability via lactate dehydrogenase release and mitochondrial activity, respectively. Interactions of AuNPs with protein components of a frequently used in vitro cell culture medium supplement, foetal calf serum, were investigated using mass spectrometry. Results Although cells internalised all AuNPs, uptake rates and specific routes of intracellular trafficking were dependent upon chitosan-functionalisation. Accordingly, an enhanced immune response was found to be chitosan-functionalisation-dependent, in the form of CCL2, IL-1β, TNF-α and IL-6 secretion, and expression ofIL -1β andNLRP3 mRNA. A corresponding increase in cytotoxicity was found in response to chitosan-coated AuNPs. Furthermore, chitosan-functionalisation was shown to induce an increase in unique proteins associating with these highly charged AuNPs. Conclusions It can be concluded that functionalisation of AuNPs with the perceived non-toxic biocompatible molecule chitosan at a high density can elicit functionalisation-dependent intracellular trafficking mechanisms and provoke strong pro-inflammatory conditions, and that a high affinity of these NP-conjugates for biomolecules may be implicit in these cellular responses.